'Right' food, 'Responsible' citizens: State‐promoted food education and a food dilemma in Japan. (27th December 2016) - Yotova, Maria
Abstract: With increasing food contamination incidences and rising concerns about food safety and the future of Japanese culinary traditions, shokuiku (food education) has become a central motif of the Japan government's food polices in recent years. Trying to navigate consumer choices amidst the increasingly globalised culinary scene and the food fear in the aftermath of the 2011 Fukushima nuclear disaster, the Basic Law on Food Education has interwoven discourses on health, the 'goodness' of local food, and the political ideologies of being responsible and patriotic citizens in support of the local economies of Japan. Through an empirical study of the school lunch system, this paper examines how food education policies have become an effective apparatus to instil state ideologies and promote national economic interests. Supposedly, shokuiku aims at promoting food knowledge, quality local foods and the health of the Japanese people, yet, against the backdrop of widespread radiation contamination fears, the rigid policies in food education have posed challenges to the state and generated a 'food dilemma' to be faced by many Japanese parents.